SALT TOLERANCE CAPACITY OF BACTERIA ISOLATED FROM IRRIGATED SOIL IN KANO, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
AbstractThis study characterized and screened NaCl tolerance in some bacterial isolates from irrigated soil of Bagwai, Kano State, Nigeria. The soil used for the study was sampled from Irrigation sites using random sampling method. The physicochemical properties and bacteriological characteristics of the soil sample were determined using culture, morphological, biochemical and molecular methods. The soil pH and electrical conductivity were 7.33 and 8.02 dSm-1 respectively. The total nitrogen and available phosphorus from the study area were 0.118% and 3.96 mgkg-1 respectively. The organic carbon recorded a very low content of 0.183%. Moisture content was 080% while temperature was found to be 29oC respectively. Bacteria isolated were identified as B subtilis, S rhizophilia and K pneumoniae. Further comfirmation using 16s rRNA sequencing showed the occurrence of Stenotrophomonas rhizophilia SBANHCu 14 (99.55%) and Klebisella pneumoniae GX 14 (98.68%). All the two bacterial isolates were able to tolerate salt concentration up to 20% but optimum tolerance was observed at 5%.
Keywords: Keywords: Salt, Tolerance, Bacteria, Irrigated Soil.